1999
DOI: 10.1017/s0007114599001750
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lipoic acid in plasma metabolites, hepatic oxygen consumption, and metabolic response to a β-agonist in broiler chickens

Abstract: The present study was conducted to determine the role of α-lipoic acid (LA) in plasma metabolites, hepatic O2 consumption, and β-adrenergic response in broilers. In Expt 1, 12-d-old female broiler chicks were divided into three dietary groups and fed on diets with or without LA (5 or 50 mg/kg) until 4 or 6 weeks of age, as a 2 × 3 factorial arrangement. The dietary LA had no effect on growth rates (body weight, abdominal fat, breast muscle, and liver). The higher level of LA increased plasma non-esterified fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
6
16
0
Order By: Relevance
“…The results obtained in the present study were consistent with previously reported results [25]. Similar findings were reported that ALA supplementation to a control diet decrease in body weight gain [26]. …”
Section: Resultssupporting
confidence: 94%
“…The results obtained in the present study were consistent with previously reported results [25]. Similar findings were reported that ALA supplementation to a control diet decrease in body weight gain [26]. …”
Section: Resultssupporting
confidence: 94%
“…These differences could also be explained by the much lower ALA doses used in our study. In fact, similar observations had been reported by others (Hamano et al, 1999; Hamano et al, 2002) which showed that 0 to 100 mg/kg of ALA did not inhibit muscle growth, but reduced body fat deposition.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, in chickens, the influence of ALA administration on hormonal actions remains unclear. Hence, the present author initially found that ALA facilitated hyperglycaemic and lipolytic responses to an intravenous infusion of isoproterenol, a b-adrenergic agonist (Hamano et al 1999(Hamano et al , 2000.…”
Section: Insulin Sensitivity: Lipoic Acid: Lipolysismentioning
confidence: 88%
“…In domestic animals, however, there are few observations on the effects on glucose and lipid metabolisms. In broiler chickens, the author has found that the metabolic response of lipids to dietary ALA administration depends on the agerelated metabolic state (Hamano et al 1999) and that simultaneous increments in both plasma NEFA and triacylglycerol, an interesting response, occurred when the level of administration rose (Hamano, 2002). Khamaisi et al (1999) also observed an increased plasma NEFA level from ALA administration in rats and suggested that this resulted from reduced hepatic fatty acid oxidation.…”
Section: Insulin Sensitivity: Lipoic Acid: Lipolysismentioning
confidence: 99%